Unilaterally blocking the muscarinic receptors in the suprachiasmatic nucleus in proestrus rats prevents pre-ovulatory LH secretion and ovulation - Vieyra, Elizabeth (Reprod Biol Endocrinol, 2016)
BACKGROUND: The suprachiasmatic nucleus (SCN) and the cholinergic system of various regions of the hypothalamus participate in the regulation of gonadotropin-releasing hormone (GnRH) and gonadotropin secretion, which are necessary for the occurrence of ovulation. In the present study, our goal was to analyse the effects of unilaterally blocking the muscarinic receptors in the SCN on ovulation and steroid secretion. METHODS: Cyclic rats were randomly allotted to one of the experimental groups. Groups of 8–14 rats were anaesthetized and microinjected with 0.3 μl of saline or a solution of atropine (62.5 ng in 0.3 μl of saline) into the left or right SCN at 09.00 or 19.00 h during diestrus-1 or on the proestrus day. The rats were euthanized on the predicted day of oestrus, and evaluated ovulation and levels of progesterone and oestradiol. Other groups of 10 rats were microinjected with atropine into the left or right SCNs at 09.00 h on the proestrus day, were euthanized eight h later, and luteinizing hormone (LH) was measured. RESULTS: At 09.00 or 19.00 h during diestrus-1, atropine microinjections into the SCNs on either side did not modify ovulation. The atropine microinjections performed at 09.00 h of proestrus into either side of the SCN blocked ovulation (right SCN: 1/9 ovulated vs. 9/10 in the saline group; left SCN: 8/14 ovulated vs. 10/10 in the saline group). The LH levels at 17.00 h in the rats that were microinjected with atropine at 09.00 h of proestrus were lower than those of the controls. In the non-ovulating atropine-treated rats, the injection of synthetic LH-releasing hormone (LHRH) restored ovulation. Atropine treatment at 19.00 h of proestrus on either side of the SCN did not modify ovulation, while the progesterone and oestradiol levels were lower. CONCLUSION: Based on the present results, we suggest that the cholinergic neural information arriving on either side of the SCN is necessary for the pre-ovulatory secretion of LH to induce ovulation. Additionally, the regulation of progesterone and oestradiol secretion by the cholinergic innervation of the SCN varies with the time of day, the day of the cycle, and the affected SCN.